2018
DOI: 10.1002/jcop.22135
|View full text |Cite
|
Sign up to set email alerts
|

Measuring national resilience: A new short version of the scale (NR‐13)

Abstract: This article is aimed at describing and validating a new short version of the National Resilience Scale (NR‐13). The available 25‐item National Resilience Scale has been employed and validated by several studies. However, the present data show that it can be substantially shortened without losing either its reliability or its validity. The new short version of the scale has been examined by the responses of an Israeli sample of adults (N = 1022). Results indicate, as expected, that national resilience promotin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 24 publications
(29 reference statements)
5
51
0
Order By: Relevance
“…The perception that the expected adaptation of governmental entities did not materialize sufficiently is strengthened by the large-scale demonstrations against the government that spread throughout Israel. Furthermore, a previous study indicated that the baseline level of patriotism was extremely high among Israelis [ 16 ]. However, an unexpected finding of the present study was a general decrease in patriotism between T1 and T2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The perception that the expected adaptation of governmental entities did not materialize sufficiently is strengthened by the large-scale demonstrations against the government that spread throughout Israel. Furthermore, a previous study indicated that the baseline level of patriotism was extremely high among Israelis [ 16 ]. However, an unexpected finding of the present study was a general decrease in patriotism between T1 and T2.…”
Section: Discussionmentioning
confidence: 99%
“…National resilience (NR). The original national scale [ 16 ] includes 13 items, whereas the scale in the present study includes 16 items. The three additional items pertain specifically to the COVID-19 crisis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…National resilience. A short version of the National Resilience Scale was employed [ 28 ]. This 13-item tool pertained to trust in national leadership, patriotism, and trust in major national institutions.…”
Section: Methodsmentioning
confidence: 99%
“…Examination of relevant literature indicates that a rather small number of studies have empirically investigated the topic of national resilience and associated it with antecedent variables (e.g., Ref. [ 28 ]. An earlier study revealed that higher levels of individual, community and national resilience have predicted lower levels of distress symptoms and higher levels of post-traumatic growth among civilians, one year after a period of conflict [ 29 ].…”
Section: Introductionmentioning
confidence: 99%